2007
DOI: 10.1128/jvi.02243-06
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Necrosis Factor (TNF) Protects Resistant C57BL/6 Mice against Herpes Simplex Virus-Induced Encephalitis Independently of Signaling via TNF Receptor 1 or 2

Abstract: Tumor necrosis factor (TNF) is a multifunctional cytokine that has a role in induction and regulation of host innate and adaptive immune responses. The importance of TNF antiviral mechanisms is reflected by the diverse strategies adopted by different viruses, particularly members of the herpesvirus family, to block TNF responses. TNF binds and signals through two receptors, Tnfrsf1a (TNF receptor 1 [TNFR1], or p55) and Tnfrsf1b (TNFR2, or p75). We report here that herpes simplex virus 1 (HSV-1) infection of TN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
55
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(61 citation statements)
references
References 71 publications
5
55
1
Order By: Relevance
“…One can hypothesize that low levels of TNFR1 are sufficient to trigger apoptosis or that TNFa signals through TNFR2 or through a third, unknown TNFR. The existence of such an unknown TNF receptor was invoked to explain how TNFa could protect against fatal HSV-1 encephalitis in TNFR1 -/-TNFR2 -/-mice [71]. A much clearer conclusion on the importance of HSV-1 R1 in counteracting DR-induced apoptosis was obtained here with respect to the Fas pathway.…”
Section: Discussionmentioning
confidence: 59%
“…One can hypothesize that low levels of TNFR1 are sufficient to trigger apoptosis or that TNFa signals through TNFR2 or through a third, unknown TNFR. The existence of such an unknown TNF receptor was invoked to explain how TNFa could protect against fatal HSV-1 encephalitis in TNFR1 -/-TNFR2 -/-mice [71]. A much clearer conclusion on the importance of HSV-1 R1 in counteracting DR-induced apoptosis was obtained here with respect to the Fas pathway.…”
Section: Discussionmentioning
confidence: 59%
“…Treatment of infected mice with neutralizing TNF-␣ antibodies increased the mortality in infected mice, suggesting an important role for TNF-␣ early in the control of virus infection in the brain, presumably through its effect on the recruitment of inflammatory monocyte/macrophage populations (38). TNF-␣ has also been shown to be protective in murine models of herpes simplex virus (HSV) encephalitis and in clearance of lymphocytic choriomeningitis virus (LCMV) (40,41). In contrast to these findings, other studies have argued that TNF-␣ facilitates WNV neuroinvasion by disrupting the integrity of the blood-brain barrier, a mechanism that may also contribute to increases in mononuclear cell infiltration into the infected CNS (42).…”
mentioning
confidence: 99%
“…TNF- has been shown to be an important cytokine in the innate immune response against various infections, including HSV. In acute infection, the lowest survival rate was observed in TNF- knock out mice infected with HSV-1 via the corneal rout [18,20]. In an encephalitis mouse model, HSV-1 was lethal to TNF- deficient mice, and the brain viral loads were higher than that in wild type mice, indicating that TNF- is a crucial factor in protection against HSV-1 infection [23].…”
Section: Discussionmentioning
confidence: 99%
“…infected spleen cells: Cantin and coworkers demonstrated that deficient of TNF- activity results in significantly increased susceptibility to fatal HSV encephalitis (HSVE) in C57BL/6 mice and prolonged persistence of elevated levels of virus in neural tissues [18]. To understand whether TNF- contributes to the basis for this reduced pathogenicity of these 2 PRV viruses in mice, we compared that the TNF- expression level in the spleen cells isolated from mice infected with wt PRV and the vhs mutant virus 41.…”
Section: Quantification Of Tnf- Expression In Prv or 41mentioning
confidence: 99%